Resistance to APC and SHBG levels during use of a four‐phasic oral contraceptive containing dienogest and estradiol valerate: a randomized controlled trial. Issue 5 (15th May 2013) - Raps, M.; Rosendaal, F.; Ballieux, B.; Rosing, J.; Thomassen, S.; Helmerhorst, F.; van, H.
Summary Background The use of combined oral contraceptives is associated with a 3‐ to 6‐fold increased risk of venous thrombosis. This increased risk depends on the estrogen dose as well as the progestogen type of combined oral contraceptives. Thrombin generation‐based activated protein C resistance (APC resistance) and sex hormone‐binding globulin (SHBG) levels predict the thrombotic risk of a combined hormonal contraceptive. Recently, a four‐phasic oral contraceptive containing dienogest (DNG) and estradiol valerate (E2V) has been marketed. The aim of this study was to evaluate the thrombotic risk of the DNG/E2V oral contraceptive by comparing APC resistance by measuring normalized APC sensitivity ratios (nAPCsr) and SHBG levels in users of oral contraceptives containing dienogest and estradiol valerate (DNG/E2V) and oral contraceptives containing levonorgestrel and ethinyl estradiol (LNG/EE). Methods We conducted a single‐center, randomized, open label, parallel‐group study in 74 women using DNG/E2V or LNG/EE, and measured nAPCsr and SHBG levels in every phase of the regimen of DNG/E2V. Results During the pill cycle SHBG levels did not differ between DNG/E2V users and LNG/EE users. nAPCsr levels were overall slightly lower in DNG/E2V users than in LNG/EE users, mean difference −0.44 (95% CI, −1.04 to 0.17) for day 2, −0.20 (95% CI, −0.76 to 0.37) for day 7, −0.27 (95% CI, −0.81 to 0.28) for day 24 and −0.34 (95% CI, −0.91 to 0.24) for day 26. Conclusion No statistical significant differences in nAPCsr and SHBG levels were found between users of the oral contraceptive containing DNG/E2V and LNG/EE, suggesting a comparable thrombotic risk